2018
DOI: 10.5194/acp-2018-1088
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The role of chlorine in tropospheric chemistry

Abstract: <p><strong>Abstract.</strong> We present a comprehensive simulation of tropospheric chlorine within the GEOS-Chem global 3-D model of oxidant-aerosol-halogen atmospheric chemistry. The simulation includes explicit accounting of chloride mobilization from sea-salt aerosol by acid displacement of HCl and by other heterogeneous processes. Additional sources of tropospheric chlorine (combustion, organochlorines, transport from stratosphere) are small in comparison. Reactiv… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2
2

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 70 publications
(122 reference statements)
0
8
0
Order By: Relevance
“…We hypothesize that including acid displacement HCl from SSA would lead to an increase in HOBr because of the competition between HOBr+Cl -(which recycles HOBr by producing BrCl) and HOBr+S(IV) (which is a sink for HOBr) in cloud droplets. Indeed, in a subsequent 265 version of GEOS-Chem, Wang et al (2018) added this source of HCl, finding an increase in BrO, especially in cloudy high latitudes. and OMI exhibit enhanced VCDtropo (3.5-5×10 13 cm -2 ) in an arc between Baffin Bay -along the west coast of Greenland -and 270 the Laptev Sea, off the Northern coast of Siberia.…”
Section: Seasonal Cycle Of Vcdtropo In the Northern Hemispherementioning
confidence: 99%
“…We hypothesize that including acid displacement HCl from SSA would lead to an increase in HOBr because of the competition between HOBr+Cl -(which recycles HOBr by producing BrCl) and HOBr+S(IV) (which is a sink for HOBr) in cloud droplets. Indeed, in a subsequent 265 version of GEOS-Chem, Wang et al (2018) added this source of HCl, finding an increase in BrO, especially in cloudy high latitudes. and OMI exhibit enhanced VCDtropo (3.5-5×10 13 cm -2 ) in an arc between Baffin Bay -along the west coast of Greenland -and 270 the Laptev Sea, off the Northern coast of Siberia.…”
Section: Seasonal Cycle Of Vcdtropo In the Northern Hemispherementioning
confidence: 99%
“…Several recent observational studies have concluded that in summertime coastal urban areas, reactions with Cl atoms dominated the early morning oxidation of alkanes before ∼10 a.m., surpassing OH reactions and that 15–25% of the total daily alkane oxidation was driven by Cl atoms (Bannan et al, ; Riedel et al, ). On a global scale, Wang et al () estimated that Cl atoms were responsible for 1% of the global oxidation of methane, and 20% of ethane, among other alkanes. Ultimately, because of the importance of Cl atoms to the overall oxidant budget in the lower troposphere, sources of Cl atoms are important to constrain.…”
Section: Introductionmentioning
confidence: 99%
“…Although the pioneering measurements of Keene et al () and Spicer et al () showed Cl 2 * (Cl 2 * = Cl 2 + HOCl) in excess of 120 pptv peaking at night, those high concentrations of Cl 2 * are thought to be driven more by HOCl than Cl 2 at night (Pszenny et al, ). Furthermore, Wang et al () significantly overestimated nighttime aircraft observations of Cl 2 during the 2015 Wintertime Investigation of Transportation, Emissions, and Reactivity (WINTER) campaign, using the global chemistry model, GEOS‐Chem, when including Cl 2 production from ClNO 2 uptake on acidic aerosols. Therefore, observations suggest that Cl 2 production from heterogeneous ClNO 2 reaction on acidic particles either occurs with a lower efficiency in the atmosphere than was measured in the laboratory, that Cl 2 production from ClNO 2 in the atmosphere is limited by a lack of aerosol having both sufficient acidity and pCl ‐ , or no observations reported to date have been made in areas where this chemistry is relevant.…”
Section: Introductionmentioning
confidence: 99%
“…The high biases of modeled surface BrO during CONTRAST and CAST may be due to the underestimate of cloud and aerosol pH. By using online aerosol pH calculation and reflecting SSA contribution to cloud pH, Wang et al (2018) found much lower BrO concentrations in tropical Pacific Ocean. Both model and observations show high values (1.9-3.0 ppt) at Tenerife Island and Cape Verde in the tropical Atlantic.…”
Section: Resultsmentioning
confidence: 89%
“…Similarly, the global mean bias is -44% in our simulation. The biases at high latitudes can be reduced by including a detail chlorine chemistry (Wang et al, 2018), since high chloride in those regions accelerate HOBr recycling by serving as a catalyst. Figure 4 also shows tropospheric BrO columns measured in in Florida, USA (Coburn et al, 2011) and derived from mean aircraft vertical profiles over the tropical Pacific from the TORERO (Volkamer et al, 2015;Wang et al, 2015;Dix et al, 2016) and CONTRAST (Koenig et al, 2017) campaigns.…”
Section: Resultsmentioning
confidence: 99%